PENGARUH MODEL PEMBELAJARAN COLLABORATIVE CREATIVITY (CC) TERHADAP KEMAMPUAN LITERASI ENERGI PADA SISWA SMA - Lu’luul Maknuniyah; Sri Astutik; Iwan Wicaksono (JURNAL PEMBELAJARAN FISIKA, 2019)
AbstractThe purpose of this research was to find out how energy literacy skills in high school students while using the Collaborative Creativity (CC) learning model. This type of research is descriptive research. This research was conducted in the even semester of the 2018/2019 academic year. Place of research in Mumbulsari 1 Public High School. The class used is class X MIPA 3 using Collaborative Creativity (CC) learning model and class X MIPA 2 using conventional models commonly used by teachers. The research instruments were observation, interviews, tests, and documentation. Analysis of research data for energy literacy skills is by using the formula for energy literacy scoring which will then be interpreted into guidelines that will be the criteria for students' energy literacy abilities. Based on the results of the analysis it can be said that the energy literacy ability of high school students while using the Collaborative Creativity (CC) learning model is good.Kata Kunci: Model Pembelajaran, Collaborative Creativity (CC), Literasi Energi